Beyond AI: Sosialisasi Dampak Sosial Kecerdasan Artifisial Dan Literasi Digital Siswa SMA Negeri 4 Kota Bengkulu - Dewantara, Ramadhan; Kartika, Shofi Dwi; Havizah, Nurul; Putri, Fhariska Dhia; Ariant, Ririn Dwi; Jumadi, Juju (Jurnal Kewirausahaan & Inovasi, 2026)
The rapid development of Artificial Intelligence (AI) necessitates digital literacy that transcends technical skills, focusing instead on its social and ethical implications. This community service program, titled "Beyond AI," aimed to enhance the critical understanding of AI's social impact among students at SMA Negeri 4 Kota Bengkulu. The participatory action research method was employed through a Four-day workshop, engaging 301 students. Activities included interactive material presentation and practical exercises on platforms facilitated by BPPTIK, covering Introduction to Cybersecurity, Introduction to Modern AI, and AI for Beginners. Results demonstrated a significant improvement in participants' understanding, with average pre-test to post-test scores increasing by 58% in algorithmic comprehension, 61% in data protection awareness, 60% in misinformation detection ability, and 72% in AI ethics understanding. The program successfully equipped students not only with knowledge but also with a critical and responsible mindset towards AI usage. This initiative underscores the urgency of integrating social and ethical dimensions of AI into digital literacy education to build students' digital resilience, preparing them to be wise and competent individuals in the artificial intelligence era. Sustainability of such programs through collaboration between academia, schools, and parents is essential for long-term impact.